Simulation-based learning using phet on the concept of series and parallel electrical circuits in secondary schools in timor-leste - Kristiani; Pedro Correia; Paulo Alves Cabral; Isabel Tina Guterres (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The teaching methods employed by instructors can vary depending on learning objectives, student profiles, and available resources. Commonly used teaching methods include traditional or conventional approaches, demonstration methods, experimental methods, and others. This study implemented a PhET simulation-based teaching project on the concept of series and parallel electrical circuits: a study involving 12th-grade students majoring in Electrical Engineering at São João Bosco Secondary School in Venilale, Timor-Leste. The study aimed to investigate students’ learning outcomes following the PhET simulation-based instruction on series and parallel circuit concepts. To achieve this objective, a survey test instrument was employed. The test was administered to 34 students. The results indicated that the calculated t-value was greater than the critical t-value (t_calculated > t_table) or (23.63 > 2.035), demonstrating a significant difference before and after the use of PhET simulations in teaching the concepts of series and parallel electrical circuits. This had a positive impact on the development of students’ knowledge.